Sustainable Systems for Livestock Production Entrepreneurship for Global Food Security: Integrating Nature-Based Solutions - Ali Farzpourmachiani; Seyedehmona Modaresrad; Mercede Ostadsandiani; Saeid Basiri; Salar Basiri; Mirmohammad Seyednouri; Mehdi Farzpourmachiani (Pandawa Institute, 2026)
Livestock production is integral to the global food chain with its physiological, nutritional, as well as economic benefits for billions of people around the world. At the same time, conventional livestock production has various environmental challenges such as production of greenhouse gas emissions, land degradation, water contamination, loss of biodiversity, among others. Nature-based solutions (NbS) have been recognized for their capability to address these challenges through the harnessing of ecological processes in livestock production activities. This review combines scientific literatures for sustainable livestock production strategies coupled with NbS for the purpose of understanding the roles of entrepreneurship in their scalability for balanced environments as well as financial viability for livestock producers worldwide. Various NbS approaches such as silvopasture practices, rotational grazing practices, agroforestry practices, integrated crop livestock production approaches, among others, have been highlighted in this review for their contribution to global food security, environment integrity, as well as rural economy development.